Yield studies of rubberwood lumber during rough miling operations. - Ratnasingam, Jegatheswaran; Scholz, Frieder (Springer Berlin / Heidelberg, 2008)
The study evaluated the processing yield of furniture-grade rubberwood (Hevea brasiliensis) sawn lumber in rough milling operations. It was found that the average rough-milling yield was 69%. Therefore, rubberwood is not a low cost material as widely perceived since its processing yield is low.